2020
DOI: 10.1101/2020.03.09.20032219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data-driven discovery of a clinical route for severity detection of COVID-19 pediatric cases

Abstract: The outbreak of COVID-19 epidemic has caused worldwide health concerns since Nov., 2019. A previous study described the demographic, epidemiologic, and clinical features for infected infants. However, compared with adult cases, little attention has been paid to the infected pediatric cases. Severity detection is challenging for children since most of children patients have mild symptoms no matter they are moderately or critically ill therein.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 6 publications
0
37
0
1
Order By: Relevance
“…Of 2696 titles, 85 studies were retained for abstract and full text screening. Twenty seven studies describing 31 prediction models met the inclusion criteria and were selected for data extraction and critical appraisal 789101112181920212223242526272829303132333435363738…”
Section: Resultsmentioning
confidence: 99%
“…Of 2696 titles, 85 studies were retained for abstract and full text screening. Twenty seven studies describing 31 prediction models met the inclusion criteria and were selected for data extraction and critical appraisal 789101112181920212223242526272829303132333435363738…”
Section: Resultsmentioning
confidence: 99%
“…One study used U.S. Medicare claims data from 2015 to 2016 to estimate COVID-19 vulnerability, 8 two studies used control CT scans from the USA or Switzerland, 11 25 and one study used simulated data. 18 All but one study 24 developed prediction models for use in adults. The median age varied between studies (from 34 to 65 years, see Supplementary Table 1), as did the percentage of men (from 41% to 61%).…”
Section: Primary Datasetsmentioning
confidence: 99%
“…One study developed a model to detect COVID-19 pneumonia in fever clinic patients (estimated C-index 0.94), 10 one to diagnose COVID-19 in suspected cases (estimated C-index 0.97), 30 one to diagnose COVID-19 in suspected and asymptomatic cases (estimated C-index 0.87), 12 one to diagnose COVID-19 using deep learning of genomic sequences (estimated Cindex 0.98), 35 and one to diagnose severe disease in symptomatic paediatric inpatients based on direct bilirubin and alaninetransaminase (reporting an F1 score of 1.00 , indicating 100% observed sensitivity and specificity). 24 Only one study reported assessing calibration, but it was unclear how this was done. 12 Predictors used in more than one model were age (n=3), body temperature or fever (n=2), and signs and symptoms (such as shortness of breath, headache, shiver, sore throat, fatigue) (n=2) (see Table 1).…”
Section: Diagnostic Models To Detect Covid-19 Infection In Symptomatimentioning
confidence: 99%
See 2 more Smart Citations